2019
DOI: 10.1016/j.eururo.2019.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Interim Results from the IMPACT Study: Evidence for Prostate-specific Antigen Screening in BRCA2 Mutation Carriers

Abstract: BackgroundMutations in BRCA2 cause a higher risk of early-onset aggressive prostate cancer (PrCa). The IMPACT study is evaluating targeted PrCa screening using prostate-specific-antigen (PSA) in men with germline BRCA1/2 mutations.ObjectiveTo report the utility of PSA screening, PrCa incidence, positive predictive value of PSA, biopsy, and tumour characteristics after 3 yr of screening, by BRCA status.Design, setting, and participantsMen aged 40–69 yr with a germline pathogenic BRCA1/2 mutation and male contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 182 publications
(164 citation statements)
references
References 31 publications
5
151
0
8
Order By: Relevance
“…Carrier men ≤55 years old seem to be considerably more susceptible to PrCa development, with an RR ranging from 7.8 to 23 [ 55 , 58 ]. Moreover, germline alterations in the BRCA2 gene have been appointed as independent predictors of a younger age of diagnosis, more aggressive phenotype, and higher mortality rate compared with non-carriers [ 55 , 59 , 60 , 61 , 62 ]. The study of germline alterations in the BRCA1/2 genes is particularly important in the identification of population-specific founder variants, e.g., in the Ashkenazim Jewish population, it is estimated that approximately 2% of the population carries at least one of three founder mutations in BRCA1 (185delA or 5382insC) and BRCA2 (6174delT) [ 63 ].…”
Section: Genetic Etiology Of Inherited Prcamentioning
confidence: 99%
“…Carrier men ≤55 years old seem to be considerably more susceptible to PrCa development, with an RR ranging from 7.8 to 23 [ 55 , 58 ]. Moreover, germline alterations in the BRCA2 gene have been appointed as independent predictors of a younger age of diagnosis, more aggressive phenotype, and higher mortality rate compared with non-carriers [ 55 , 59 , 60 , 61 , 62 ]. The study of germline alterations in the BRCA1/2 genes is particularly important in the identification of population-specific founder variants, e.g., in the Ashkenazim Jewish population, it is estimated that approximately 2% of the population carries at least one of three founder mutations in BRCA1 (185delA or 5382insC) and BRCA2 (6174delT) [ 63 ].…”
Section: Genetic Etiology Of Inherited Prcamentioning
confidence: 99%
“…International guidelines recommend annual PSA screening for PCa in the general population between 40-45 years of age [64]. The IMPACT study evaluated the efficacy of this screening approach in patients with BRCA germline mutations [65]. That study found that patients with the BRCA2 mutation were diagnosed at a younger age and also more likely to present clinically-significant disease at diagnosis (intermediate or high-risk PCa in 77% of BRCA2 carriers versus 40% in controls).…”
Section: Biomarkers Of Susceptibilitymentioning
confidence: 99%
“…Following the first round of screening, it has shown no difference between BRCA1/2 mutation carriers and controls in the rate of detection of prostate cancer or the positive predictive value of prostate biopsy in men with a PSA ≥ 3 ng/mL. However, no conclusions can be made until more follow-up data are collected [95].…”
Section: Genetic Testing and Prostate Cancermentioning
confidence: 99%